Collaborative engineering as a basic concept for teaching structuration. (27th July 2009) - Bernard, A.; Perry, N.; Depince, P.
Engineering education is evolving in a global context. Projects activities allow students structuring and applying the knowledge learned while facing problems. But, when taking into account MultiDisciplinary Optimisation (MDO), it is necessary to model and to exploit the all context and technical constraints. Two elements lead such approach. First of all, roadmaps give structured processes for the resolution of project objectives. Then, MDO allows solving local problems. The collaborative engineering needs to achieve the final choices based on the indications of strategic inputs, roadmaps and MDO results. This paper relates concrete experiences and proposes some progress for future engineering education.